Influence of Genetic Polymorphisms Involved in the Hypothalamic–Pituitary–Adrenal Axis and their Interactions with Environmental Factors on Antidepressant Response - Geng, Lei‐Yu (CNS Neurosci Ther, 2014)
AIMS: To investigate the role of genetic polymorphisms in candidate genes associated with the HPA axis and their interactions with environmental stressors in antidepressant response. METHODS: The remission of depressive symptoms after 8 weeks of antidepressant treatment was tested against 21 single nucleotide polymorphisms (SNPs) in five candidate genes associated with the HPA axis in a Chinese Han sample suffering from unipolar depression (n = 273). Any history of childhood trauma and recent negative life events were measured using the Childhood Trauma Questionnaire‐Short Form (CTQ‐SF) (n = 206) and the Life Event Scale (48 item, LES) (n = 207), respectively. Reporter gene assays were used to evaluate the possible effects of the most significant SNP on gene expression. RESULTS: A functional polymorphism at 3′UTR of the corticotropin‐releasing hormone receptor 1 (CRHR1) gene (rs28364032) and three haplotypes containing it showed significant relationships with antidepressant remission. Further laboratory‐based genomic studies showed that the G‐to‐A change of rs28364032 resulted in a 10–12% decrease in the intensity of luciferase activity. However, we failed to find association of environments and their interaction with HPA system‐related genes with antidepressant remission. CONCLUSIONS: Our results support a definite role for CRHR1 in the pharmacogenetics of antidepressant drugs. This may contribute to interpatient differences in their responses to antidepressant drugs.